Left aberrant subclavian artery. Systematic study in adult patients. (1st August 2017) - Tyczyński, Paweł; Michałowska, Ilona; Wolny, Rafał; Dobrowolski, Piotr; Łazarczyk, Hubert; Rybicka, Justyna; Hoffman, Piotr; Witkowski, Adam
Abstract: Background: Left aberrant subclavian artery (LASA), is a type of right aortic arch (RAA) branching, which takes-off distally to the right subclavian artery and usually crosses behind the esophagus to the left upper limb. Taking into account the rarity of RAA, LASA is much more rarely seen than the right aberrant subclavian artery (RASA) originating from the left aortic arch. However, RAA may be associated with much more frequent presence of LASA, than left aortic arch with RASA. Anatomical LASA characteristics were not described up to date. Methods: Individual patient records filed in the electronic database from a single high-volume tertiary cardiac center were retrospectively screened for the presence of RAA in the consecutive patients who underwent chest computed tomography from 2008 to 2016. Results: 14 patients with LASA were identified. Only 3 were free of coexisting intra- or extra-cardiac anomalies. The most common defect was tetralogy of Fallot (3 patients). One patient had five congenital defects. Kommerell's diverticulum (KD) was present in 9 patients. In all patients the LASA course was retrotracheal and retroesophageal. In all but one patients esophageal modelling or compression by KD or LASA was present. Conclusions: Knowledge of Kommerell's diverticulum presence and morphology as well as the LASA course during preinterventional work-up of patients with congenital heart defects is critical, since it may have surgical implications during corrective procedures.